A review on enhanced mixing methods in supersonic mixing layer flows. (November 2018) - Tan, Jianguo; Zhang, Dongdong; Lv, Liang
Abstract: The development of supersonic and hypersonic aeronautical projects has led to a renewal of interest and research in supersonic mixing processes and methods to control them. Due to the compressibility effects, the mixing process in supersonic condition is significantly inhibited. Limited flow residence time (at the order of microseconds) for mixing of supersonic airstream and fuel in a scramjet combustor calls for the development of techniques for mixing enhancement. In the present paper, the applicable techniques for mixing enhancement of supersonic mixing layer flows are reviewed comprehensively. Following the brief introduction of fundamentals of supersonic mixing layer, this paper discusses the mixing enhancement methods in the categories of: passive flow control techniques, active flow control techniques and shock wave induced mixing enhancement strategy. Based on the review of former progress, the gaps in current knowledge and areas where more research is needed are pointed out. Meanwhile, the mechanisms of different enhanced mixing methods are summarized, which can be a reference and guidance for the future techniques design for mixing enhancement of supersonic flows. Highlights: Enhanced mixing methods for supersonic mixing layers are reviewed. Overview of the fundamentals of supersonic mixing layers is presented. The mechanisms of different methods for mixing enhancement are revealed. The present review can be a reference and guidance for future strategy design.